Short forms of the Utrecht-Management of Identity Commitments Scale (U-MICS) with the domains of job, romantic relationship, and region. (January 2017) - Schubach, Elisabeth; Zimmermann, Julia; Noack, Peter; Neyer, Franz J.
Abstract: The U-MICS is a self-report questionnaire designed to assess the identity dimensions from a domain-specific perspective. The present study reports on the development of a short-form version for the domains of job and romantic relationship in young adults from Germany and extends this scale to include the domain of region ( n Sample1 = 95, 84% female, mean age 22.45 years; n Sample2 = 1, 795, 71% female, mean age 24.53 years). We found the short form to possess adequate psychometric properties and to demonstrate a factor structure congruent to the long-form version. Regarding validity, the small correlations across domains within dimensions support a domain-specific approach to identity. The associations between the different identity domains with personality traits are similar, indicating a consistent pattern of convergent validity for all domains. We conclude that "region" provides a valuable complement to the established domains that can all be reliably assessed with the U-MICS–Short Form.